Hipercortesía verbal en Eurípides - Rodríguez-Piedrabuena , Sandra (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2020)
This paper presents an overview of the theoretical background on over- and under-politeness as well as on conventionalised irony. It goes on to explore these phenomena in relation to a collection of suppliant scenes by Euripides, since they are easy to compare in terms of the narrative pattern and the role performed by the characters. Along with other examples from the sample, this article attempts to propose that the idioms οὐκ οἶδ’ ἐγώ ‘I am not aware that’, ὡς ἔοικε ‘it seems’ and βούλῃ (+ subj. / acI); ‘do you want…?’, εἰ βούλῃ ‘if you want’ are likely cases of conventionalised overpoliteness.